Scientific selection and breeding method for increasing the milk production - Deb, Rajib; Raja, T V (Indian Farming, 2020)
Dairy cattle rearing is the backbone of Indian rural economy as it provides employment opportunity, steady income and nutritional security to the rural farmers mainly consisting of small and marginal and landless labourers. Cattle rearing in India is considered as subsidiary enterprise to agriculture as the cattle are maintained mainly on grazing in the available agricultural/barren land or the agricultural by-products. Cattle provide milk for human consumption, draught power for agricultural operations and dung as manure and fuel. The sustainability and profitability of cattle rearing is mainly based on the scientific.